Penegakan Hukum Terhadap Penyelenggara Jalan Rusak Yang Mengakibatkan Kecelakaan Lalu Lintas - Abdul Wahab Harun; Dian Ekawaty Ismail; Jufriyanto Puluhulawa (Hakim, 2024)
The aim of this research is to determine law enforcement against operators of damaged roads which result in traffic accidents and to find out what are the obstacles in implementing law enforcement against operators of damaged roads which result in traffic accidents. This research uses an empirical legal research method where the researcher uses a statutory approach and a case approach and data collection is carried out using literature studies and interviews. The results of the research show: firstly, the police in the Bone Bolango Police area carry out law enforcement against drivers who maintain damaged roads that cause accidents. traffic in a preventive and repressive manner. Bone Bolango Regency Police have been carrying out repressive actions such as education and legal action; However, due to a number of obstacles experienced by the Bone Bolango Police, no legal action can be taken until the trial, which only requires making a case report. Both the internal and external operational environment of the traffic police are some of the challenges faced by the Bone Bolango Police. The Bone Bolango Police Traffic Accident Unit lacks personnel and expertise, and the officers' attitude towards drivers is less firm. One of the internal problems faced by the traffic police is this problem. Public ignorance of laws and regulations related to damaged roads and lack of community involvement in reporting damaged roads are two examples of external variables handled by the Traffic Police. Apart from that, there is ambiguity in Law Number 22 of 2009 concerning Road Transport and Traffic. The meaning of "road managers" and the difficulty of law enforcement in enforcing these regulations, especially Article 273, which emphasizes the importance of considering the potential legal consequences for "road managers" who fail to repair damaged roads immediately, which can result in traffic accidents.